Improving the Medical Assessment of Patients Before Electroconvulsive Therapy: An Audit Across Two Sites. Issue 2 (June 2016) - Driver, Hannah R.
Abstract : Objective: It is essential that a medical assessment is completed before commencing electroconvulsive therapy (ECT) to identify possible risk factors that may complicate anesthesia. This audit aimed to improve the physical examination and documented medical history of this assessment usually performed by referring psychiatrists. Methods: Patients from 2 sites (A and B) were retrospectively audited against standards from the Scottish ECT Accreditation Network. The timing and systems examined for the physical examination were noted. Site A used an examination sheet; at site B there was no standard way of recording examination. Documented medical histories were compared with comprehensive histories obtained using multiple sources. Discrepancies were noted. Site A was reaudited after amending the examination sheet and adding prompts to use multiple sources when gathering histories. Results: There were repeat examinations for ECT in 30 patients (100%) at site A and 6 (23%) of 26 at site B. Physical examinations were incomplete in 47% of patients at A and 100% at B. Oral examination was frequently missed at both sites. Medical histories were accurate in 20% at A and 38% at B. In the reaudit of site A, all 12 patients had a complete repeat examination; histories were accurate in 8 (67%), with multiple sources used in 11 (92%). Conclusions: Incomplete or inaccurate assessments put patients at risk. Oral examinations should be part of initial medical assessments. This audit shows the benefits of using a physical examination sheet to ensure a repeat complete examination. Using multiple sources to gather medical histories is encouraged.